Sulfide Removal by Oxidation Treatment of Tannery Wastewater - Salas C., Gilberto (2005)
In this work is presented sulfide oxidation to sulfate of effluents from the tanning industry. During sulfide oxidation, sulfide bearing liquors can be separated from effluent using air oxidation, catalytic air oxidation, and direct chemical oxidation. This operation controls the release of hydrogen sulfide from beam house wastes and others sulfide bearing effluents pH = 13. Catalytic oxidation is a simple, low-cost technology which used aeration in presence of a manganese catalyst (i.e., 3,2 mg MnSO4/mg S-2). After six hours of oxidation the concentration of sulfide is reduce to 98% (470 a 5 mg/L). When used, approximately 60 m3 of air is needed for each m3 of effluent. The efficiency of aerator used after sex hours is 98%.